2016
DOI: 10.1007/s10457-016-9896-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating carbon storage in windbreak trees on U.S. agricultural lands

Abstract: Assessing carbon (C) capture and storage potential by the agroforestry practice of windbreaks has been limited. This is due, in part, to a lack of suitable data and associated models for estimating tree biomass and C for species growing under more opengrown conditions such as windbreaks in the Central Plains region of the United States (U.S.). We evaluated 15 allometric models using destructively sampled Pinus ponderosa (Lawson & C. Lawson) data from field windbreaks in Nebraska and Montana. Several goodness-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 46 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…Likewise, statistical models also have been used to estimate carbon sequestration in shelterbelts [10,50]. Possu et al [78] assessed 15 allometric models on Ponderosa pine windbreaks and used the best model to estimate carbon sequestration for 16 shelterbelt tree species in Nebraska, projected over 50 years in nine areas of the U.S. They found that carbon sequestration potential ranged from 1.07 ± 0.21 to 3.84 ± 0.04 Mg C ha −1 year −1 for conifer species and from 0.99 ± 0.16 to 13.6 ± 7.72 Mg C ha −1 year −1 for broadleaved deciduous species.…”
Section: Shelterbelt Carbon Sequestration Potential and Stocks Above-mentioning
confidence: 99%
“…Likewise, statistical models also have been used to estimate carbon sequestration in shelterbelts [10,50]. Possu et al [78] assessed 15 allometric models on Ponderosa pine windbreaks and used the best model to estimate carbon sequestration for 16 shelterbelt tree species in Nebraska, projected over 50 years in nine areas of the U.S. They found that carbon sequestration potential ranged from 1.07 ± 0.21 to 3.84 ± 0.04 Mg C ha −1 year −1 for conifer species and from 0.99 ± 0.16 to 13.6 ± 7.72 Mg C ha −1 year −1 for broadleaved deciduous species.…”
Section: Shelterbelt Carbon Sequestration Potential and Stocks Above-mentioning
confidence: 99%
“…Furthermore, the vegetation C sequestration rate differs by forest types. As an example, within windbreak systems, broadleaved trees demonstrated an almost double C storage capacity (4.39 ± 1.74 Mg C ha −1 y −1 ) than conifer trees (2.45 ± 0.42 Mg C ha −1 y −1 ) in a study involving nine ecoregions across the USA [26]. Table 1.…”
Section: Role Of Agroforestry In C Sequestration and Reducing Greenhomentioning
confidence: 99%
“…Like native forests, agroforestry has the ability to sequester large amounts of carbon especially for the small amount of land area occupied by these practices (Table 3) (Schoeneberger et al 2017b). Carbon storage (aboveground and belowground) rates in North and South Dakota, Nebraska, and Kansas have been estimated to be around 3 Mg C ha −1 for deciduous and conifer windbreaks (Possu et al 2016), which is greater than agricultural In terms of relative contribution within a field, inclusion of a windbreak (comprising 3-5% of a field) for purposes other than mitigation services, can potentially almost double the total carbon sequestered from converting a field from conventional to no-till after 50 years (Schoeneberger 2009). Indirect carbon and other greenhouse gas contributions from agroforestry, such as emission avoidance in fields and energy savings from farmstead windbreaks, may be even greater than that from carbon sequestration (Ballesteros- Possu et al 2017).…”
Section: Mitigation-native and Agricultural Forests As A Climate Chanmentioning
confidence: 99%